SYSTEMATIC LITERATURE REVIEW: PEMANFAATAN TEKNOLOGI AUGMENTED REALITY (AR) DALAM PEMBELAJARAN BERBASIS KEARIFAN LOKAL UNTUK MENGUATKAN LITERASI BUDAYA SISWA SEKOLAH DASAR - Anugrah Wardani, Femy; Sumartiningsih, Sri; Avrilianda, Decky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine how the utilization of Augmented Reality (AR) technology can integrate learning with local wisdom to strengthen students cultural literacy. The background of this research stems from the rapid development of learning media, which has increasingly shifted toward the use of digital technologies, one of which is Augmented Reality. The combination of AR technology and elements of local wisdom can serve as an effective medium for students to understand the cutural values of their region. The implementation of AR-based learning that incorporates local wisdom is also considered a relevant pedagogical approach to enhance student engagement in elementary schools. Through this strategy, learning activites not only become more engaging and interactive, but also foster motivation and help students develop positive character from an early age. This research employs the SLR method using the PRISMA approach, which involves collecting, selecting, and analyzing relevant research findings. Out of a toal of 40 reviewed articles, 10 were identified as the most suitable to serve as primary sources for this study. The findings indicate that AR-based learning can enhance students cultural literacy while making the learning process more interactive and meaningful. AR-based media help students understand cultural values through concrete and engaging visual experiences.